Indentification of Causes of Scabies on Santri of Popular Dayah Educational Institutions in Aceh Province - Evi Dewi Yani (Jurnal Serambi Ilmu, 2022)
Scabies is an infection with mites (Sarchoptes scabies) that cause small redbumps on the skin. Scabies is caused by poor personal hygiene. Scabies orscabies disorders always start from itching on the skin caused by the scabiesmite (Coptes scabei), transmission of scabies lice can occur due to directtransmission, for example in contact with sufferers or indirectly, such asthrough clothing, blankets, and towels. This study aims to analyze thefactors that influence the incidence of scabies in traditional dayah santri inAceh Besar district. The research was conducted using a qualitative methodwith the respondents of traditional dayah students in Aceh Besar. data onsanitation, bathrooms, toilets, room area, room humidity were carried out byethnographic observations and direct interviews. The results of thequalitative research and direct observation in the dayah showed that thesanitation facilities were still inadequate in the dayah. Such as the number ofoccupants in one room which reaches more than 8 people in a roommeasuring 4 x 4 meters. Poor sanitation also seems to play a major role inthe incidence of scabies in students. In addition, the personal hygienebehavior of students such as changing towels and bathing facilities whichare less in number when compared to the number of students alsoaccelerates the spread of scabies.